Farming for the future: Understanding factors enabling the adoption of diversified farming systems - Sanchez-Bogado, Andrea Cecilia; Estrada-Carmona, Natalia; Beillouin, Damien; Chéron-Bessou, Cecile; Rapidel, Bruno; Jones, Sarah (Elsevier, 2024)
Diversified farming practices offer a promising pathway to sustainable food production by providing economic, environmental, and social benefits to farmers and society. However, the factors influencing their adoption are poorly understood, hindering the development of effective promotion strategies. This study presents a comprehensive global meta-analysis of 154 peer-reviewed studies analysing factors influencing adoption. We examined the effects of 71 factors across nine key categories—biophysical context, farm management characteristics, farmers’ attitudes, political and institutional context (access to knowledge, land tenure, financial risk management), and five forms of capital (financial, human, natural, physical, and social)—on the adoption of ten diversified practices in 42 countries across five UN regions.